Metode Clustering K-Medoids untuk Aplikasi Pembelajaran di Masa Pandemi COVID-19 - Sari, Miranda; Munthe, Ibnu Rasyid; Irmayani, Irmayani (LPPM UNIKA Santo Thomas Medan, 2021)
The central government took a policy to carry out social distancing with this social distancing having an impact on all activities such as having an impact on the learning process that usually takes place in the classroom turning into online learning using several supporting applications in the learning process during the Covid 19 pandemic. Such as using WhatsApp, Moodle , and Zoom for the learning process. Of the three applications commonly used by students and lecturers for the learning process, it can be grouped using the K-Medoids method which will get a cluster of preferred and disliked applications. The researcher took data from a questionnaire made with Google Form which was distributed to 100 students who often did the learning process with the three applications. Can produce a grouping of applications that students like and dislike in the learning process. By looking at the level curve in Figure 7. There are two clusters of red and blue. If the curved line to the right increases, there are many things that are not liked in the application used. Conversely, if the line from the curve to the right decreases, then online applications are less favorable. The results of this study can be seen from the curve picture that learning is most prioritized in the learning process during the Covid 19 pandemic using the Moodle and WhatsApp applications, and the use of zoom is not prioritized in the learning process. if the line from the curve to the right decreases, then online applications are less favored. The results of this study can be seen from the curve image that learning is most prioritized in the learning process during the Covid 19 pandemic using the Moodle and WhatsApp applications, and zooming is not prioritized in the learning process. if the line from the curve to the right decreases, then online applications are less favored. The results of this study can be seen from the curve picture that learning is most prioritized in the learning process during the Covid 19 pandemic using the Moodle and WhatsApp applications, and the use of zoom is not prioritized in the learning process.